2019
DOI: 10.1136/bmjopen-2019-029236
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of disease prevention and management interventions in food pantries and food banks: a scoping review

Abstract: ObjectiveFood insecurity affects millions of Americans and is associated with a range of adverse health outcomes. Food insecure individuals often obtain food from food pantries/banks, prompting health researchers to implement disease prevention/management interventions at these sites. This review examined the existing peer-reviewed research on disease prevention/management interventions implemented in food pantries/banks.DesignScoping review.Data sourcesDatabases searched included MEDLINE, Web of Science, CINA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
(142 reference statements)
3
15
0
Order By: Relevance
“…Our sample of 196 urban food bank users who responded to the qualitative questions consisted of mainly non-married, very low-income adults with high burden of reported chronic illness. These findings align with reported demographics of urban food bank users (Long et al, 2019; Loopstra, 2018), suggesting that food banks are highly utilized among adults with low SES status and sub-optimal physical health. Our participants reported a high burden of chronic illness such as obesity, mental illness, and chronic pain.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…Our sample of 196 urban food bank users who responded to the qualitative questions consisted of mainly non-married, very low-income adults with high burden of reported chronic illness. These findings align with reported demographics of urban food bank users (Long et al, 2019; Loopstra, 2018), suggesting that food banks are highly utilized among adults with low SES status and sub-optimal physical health. Our participants reported a high burden of chronic illness such as obesity, mental illness, and chronic pain.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, some participants in our study reported a need for increased knowledge on how to cook foods offered at the food bank or to purchase healthy food on a budget. Nurses could advocate for directors of food banks to offer cost-conscious, healthy cooking or food budgeting education—a strategy that has been reported as helpful in this population (Dave et al, 2017; Long et al, 2019). Nurses are well-positioned to advocate on a community, national, and global policy level for improved accessibility and affordability of healthy foods for socioeconomically disadvantaged adults using existing food bank services.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Food pantries offer an alternative to MTMs at lower cost and without the need for staff to prepare and deliver meals. A food pantry is defined as any food organization that provides unprepared food to individuals in need ( Long et al, 2019 ). Medical food pantries (MFPs), focus on providing food packages or bags tailored to support chronic disease management and promote health rather than addressing hunger alone.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, interventions in the form of food pharmacy programs are connecting patients with food and nutrition resources within medical facilities [ 42 , 43 ]. Medical interventions are surfacing and have shown promise in food pantry settings [ 44 ]. Within the pantry setting, disease specific interventions (e.g., diabetes management interventions) have shown success among pantry clients [ 22 , 45 ].…”
Section: Discussionmentioning
confidence: 99%